2014
DOI: 10.1590/1519-6984.25712
|View full text |Cite
|
Sign up to set email alerts
|

The orchid-bee fauna (Hymenoptera: Apidae) of a forest remnant in the southern portion of the Brazilian Amazon

Abstract: The orchid-bee fauna of the region of Porto Velho, in the state of Rondônia, Brazil, close to the southernmost limits of the Amazon Basin, was surveyed for the first time using five different scents as baits to attract orchid-bee males. Five hundred and twenty-one males belonging to five genera and 29 species were collected with bait traps during 26 non-consecutive days from November, 2011 to January, 2012. Eulaema nigrita Lepeletier, 1841 and Eulaema meriana (Olivier, 1789) were the most common species in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…We checked the species distribution recorded in our research with information available on the literature for Neotropical region (Dressler, 1982a, b, c;Hinojosa-Díaz and Engel, 2014;Oliveira, 2006Oliveira, , 2007Ramírez et al, 2002Ramírez et al, , 2015, Brazilian Amazon Morato, 2004, 2006;Nemésio, 2005;Oliveira and Campos, 1995;Oliveira and Nemésio, 2003;Santos-Júnior et al, 2014;Storck-Tonon et al, 2009; Atlantic Forest and Cerrado (Nemésio, 2009(Nemésio, , 2010(Nemésio, , 2012bSilveira, 2007, 2010;Nemésio and Faria-Junior, 2004;Oliveira-Junior et al, 2015;Silva, 2012); and current studies carried out on the states of Pará and Maranhão (Antonini et al, 2017;Brito et al, 2017; Brito and Rêgo, Table 1. Composition, number of specimens recorded, frequency of occurrence (FO), dominance (D) and category (CAT) of orchid bees from entomological collections, with occurrence in the municipalities of Belém Endemism Center, eastern Amazon, Brazil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We checked the species distribution recorded in our research with information available on the literature for Neotropical region (Dressler, 1982a, b, c;Hinojosa-Díaz and Engel, 2014;Oliveira, 2006Oliveira, , 2007Ramírez et al, 2002Ramírez et al, , 2015, Brazilian Amazon Morato, 2004, 2006;Nemésio, 2005;Oliveira and Campos, 1995;Oliveira and Nemésio, 2003;Santos-Júnior et al, 2014;Storck-Tonon et al, 2009; Atlantic Forest and Cerrado (Nemésio, 2009(Nemésio, , 2010(Nemésio, , 2012bSilveira, 2007, 2010;Nemésio and Faria-Junior, 2004;Oliveira-Junior et al, 2015;Silva, 2012); and current studies carried out on the states of Pará and Maranhão (Antonini et al, 2017;Brito et al, 2017; Brito and Rêgo, Table 1. Composition, number of specimens recorded, frequency of occurrence (FO), dominance (D) and category (CAT) of orchid bees from entomological collections, with occurrence in the municipalities of Belém Endemism Center, eastern Amazon, Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…The number of published studies showing the species composition of orchid bee fauna in the states of Pará and Maranhão is still less significant (Brito and Rêgo, 2001;Silva and Rebêlo, 1999) and most of them are small inventories carried out in very specific localities (Maués et al, 2012;Moura et al, 2011;Santos et al, 2011;Pereira et al, 2014;Taniguchi et al, 2012). Although recent studies have been taken on the state of Pará, addressing the effects of land use, isolation and climate changes on orchid bee assemblages, they are concentrated in the southeast and western of the state of Pará, outside of the BEC domain (Antonini et al, 2017;Brito et al, 2017;Solar et al, 2016), and ours is the first to addresses the rescue of historical records of these bees in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Malaise traps may not be the most appropriate sampling method for bees. Although showed as highly effective for parasitoids (Mazón and Bordera 2008) and aculeates in general (Volpato et al 2020), with some reported bias either towards males (Aguiar and Santos 2010) or females (Mazón et al 2020), scent-baited traps or entomological nets seem to work better for bees (Santos Júnior et al 2014;Ferronato et al 2018;Alvarenga et al 2020). Other sampling methods should be used to complement Malaise traps, especially when time for field work is brief (McGravy et al 2016;Saunders and Ward 2018).…”
Section: Discussionmentioning
confidence: 99%
“…De forma geral, vanilina e eugenol têm se mostrado bastante atrativas em diversos estudos (PERUQUETTI et al, 1999;OLIVEIRA JUNIOR et al, 2015;SANTOS JÚNIOR et al, 2014). No presente trabalho, vanilina foi a isca odorífera com mais preferência, atraindo maior número em abundância de indivíduos, seguida por eugenol que atraiu maior número em riqueza de espécies, e a menos atrativa foi geraniol.…”
Section: Preferência Por Iscas Odoríferasunclassified
“…Alguns estudos também obtiveram resultados semelhantes em relação à maior número de espécies atraídas pela isca eugenol e espécimes por vanilina, ou vice-versa. Santos Júnior et al (2014), também observaram resultado semelhante, onde eugenol atraiu maior número de espécies. Ferreira et al (2011), observou em seu estudo resultado oposto, onde as armadilhas com eugenol coletaram maior número de espécimes, enquanto vanilina atraiu maior número de espécies.…”
Section: Preferência Por Iscas Odoríferasunclassified